AB0810 INTRA-ARTICULAR CNTX-4975 FOR PAINFUL KNEE OSTEOARTHRITIS: ASSESSMENT OF COOLING METHODS FOR REDUCING PROCEDURAL PAIN. (June 2019) - Stevens, Randall; Guedes, Kimberly; Mistry, Nilam; Lascelles, Duncan; Ball, David
Abstract : Background: CNTX-4975 is a long-acting, trans -capsaicin injection in phase 3 trials for treatment of moderate to severe pain associated with knee osteoarthritis (OA). Intra-articular (IA) CNTX-4975 injection produces short-lived procedural pain that can be ameliorated with joint cooling. A prior analysis (Cohort 2) demonstrated that a circumferential circulating ice water wrap (CCIWW) more effectively lowered IA knee temperature and reduced procedural pain than an ice pack on top of the knee (3.4 vs 7.3, respectively, on a numeric pain rating scale [NPRS] 10 minutes post-CNTX-4975). Objectives: Subjects were enrolled in 2 separate cohorts (C3/C4) to: compare effects of 2 circumferential cooling methods on IA and skin knee temperature and procedural pain (C3); and assess procedural pain with an abbreviated cooling schedule and with vs without post-CNTX-4975 cooling (C4). Methods: Eligible subjects were adults aged 45–75 yrs with ≥3 months of bilateral moderate to severe OA knee pain. All subjects received each cooling device on opposite knees; IA CNTX-4975 injections and other procedures on the left and right knees were separated by 7 (±2) days. See Figure for study design. IA and skin temperatures were recorded throughout the procedures. Subjects rated procedural pain at prespecified times using NPRS (0=no pain; 10=worst possible pain). Results: Five subjects enrolled in and completed each cohort (mean age, yrs: C3, 57.6; C4, 59.6; each 80% male). In C3, mean IA temperatures decreased with both methods; mean temperatures at baseline and 105 minutes were 33.7°C and 26.7°C for ice-gel pack cooling and 32.4°C and 28.2°C for CCIWW. Skin temperature reductions between cohorts were similar; mean temperatures were 28.8°C and 14.3°C (ice-gel pack) and 28.7°C and 15.2°C (CCIWW). Mean IA temperatures in C4 at baseline and 55 minutes (15 minutes post-CNTX-4975 and/or end of last cooling period [CCIWW only]) were 33.6°C and 29.0°C for ice-gel pack cooling and 32.1°C and 27.7°C for CCIWW. Mean skin temperatures were 28.5°C and 22.8°C for ice-gel pack and 27.8°C and 18.8°C for CCIWW. Pain levels before CNTX-4975 were low. Procedural pain peaked 10–20 minutes after CNTX-4975 injection in both cohorts. While mean pain levels were similar across cohorts (Table ), pain was reduced more effectively by CCIWW in C3 and ice-gel pack in C4. Procedural pain was not increased in the absence of post-injection cooling in C4. Conclusion: The ice-gel pack and CCIWW effectively reduced IA knee joint temperatures and procedural pain in both cohorts. Shorter cooling time and low pain levels observed with IA CNTX-4975 and ice-gel pack cooling in C4 suggest that this strategy may be feasible in clinical practice. Disclosure of Interests: Randall Stevens Shareholder of: Centrexion Therapeutics Corp, Employee of: Centrexion Therapeutics Corp, Kimberly Guedes Employee of: Centrexion Therapeutics Corp, Nilam Mistry Employee of: Centrexion Therapeutics Corp, Duncan Lascelles Consultant for: Centrexion Therapeutics Corp, David Ball: None declared